Challenges and Opportunities for Girl Child Education Under the National Policy of Education in Cross River State - Eyong, Victoria Amiokama; Yamma, Abdullahi Mohammed; Sunday, Jacho David (Kashere Journal of Politics and International Relations, 2024)
The issue of girl child education in Nigeria has been a persistent challenge, despite efforts to address it through various national policies. The National Policy on Education, introduced to promote equal educational opportunities for all children in Nigeria, has not been uniformly successful in ensuring access to quality education for girls. Research indicates that socio-cultural, economic, and political factors continue to undermine the implementation of policies aimed at enhancing girl child education in many parts of Nigeria, including rural areas where traditional norms still play a dominant role. Yet, existing studies lack clarity on the cultural factors driving this change. This paper examined challenges and opportunities for girl child education under the national policy of education in Cross River State. The paper used 7,500 respondents with a sample size of 347, determined using Krejcie and Morgan. Data collection utilised a self-structured questionnaire, and analysis employed descriptive statistics like frequency count and mean. The findings suggest that parents' religious convictions impact the girl child education, and cultural ideas also play a role. Strategies to enhance cultural and religious beliefs on girl-child education include mandating education, increasing female representation in chosen roles, and promoting awareness programme. The study recommends encouraging girls to attain basic education for independence and a brighter future.